Analisis Tingkat Keusangan dan dan Paro Hidup Literatur Monograf yang Disitir pada Skripsi Mahasiswa Program Studi Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi Tahun 2017-2020 - Pangastuti, Martha Galuh Ari; Dastina, Wenny (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2021)
Introduction This study aims to determine the level of obsolescence and half-life of monograph literature used in thesis writing for students of the Library Science Department, Faculty of Adab and Humanities, UIN Sulthan Thaha Saifuddin Jambi. This is on top of the importance of using new literature in every scientific writing to show progress or developments in the field of science. Research methods. The research uses quantitative methods with a bibliometric approach. Data analysis. data analysis using bibliometric analysis formula in finding the level of obsolescence and half-life of documents. Results and Discussion. The results show that the highest level of literary obsolescence is found in the thesis in 2019 with a percentage of 55.87% of the 571 books cited, which are 319 books, and the lowest level of obsolescence is found in the thesis in 2017 with a percentage of 46.22% of the 357 cited books, namely a total of 165 books. While overall from 2017-2020 the average obsolescence rate obtained was 50.89%. For the level of up-to-date literature is 49.31% based on the average age of the half-life obtained, which is 10.39 years. Conclusions and suggestions. Looking at the percentage of monograph literature used in student thesis writing, there are 49.31% new literature and 50.89% obsolete literature. So it can be said that more than half of the monograph literature used in student research is not up-to-date. Libraries located in higher education institutions at the level or level that have the skills to meet user needs, especially in making thesis by providing the latest literature can present up-to-date and useful information in the development of science, especially in the field of Library Science.